FROM HUMAN RESOURCE TO HUMAN REAL SOURCE (Spiritual Management Perspective) - Reza Arfiansyah (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2019)
Humans are God's creation, while science comes from human thought. One example of science is management science. There have been many management theories that have been delivered in a timely manner by management experts, such as the Theory of Human Resources (HR), Human Resource Management (HRM), and Strategic Human Resource Management (MSDMS). We have been busy discussing the management, but forgot about the study of man (human). For this reason, the relationship between man-management-money is inseparable, especially the man. The study of "humans" in HR, HRM, and MSDMS has resulted in concepts such as Human Resource Management (HRM), Holistic Human Resource Management (HHRM), Human Capital Management (HCM), and Spiritual   Capital   Management  (SCM).   Different  from   these   concepts,   with   the   3M   (Man- Management-Money) spiritual management approach, the author offers the concept of Human REALsource (HRs), Management by Heart, and Beyond Success. Keywords: Human Resource, Human REAL-source, Spirituality